Fishmeal-Based Media Supports Growth and Endospore Production of Locally-Isolated Lysinnibacillus sphaericus and Induces its Toxicity to 3rd Instar Aedes aegypti Larvae in Laboratory Conditions - Bambang Fajar Suryadi; Ika Mustikasari; Zuriatun Annisa; Sarkono; Galuh Tresnani (Postgraduate, University of Mataram, 2024)
The aim of this study was to determine whether fishmeal-based media could be used to grow L. sphaericus and induce its toxicity against Aedes aegypti larvae. Three concentrations (10, 20 and 30%) of fishmeal-based media were used to grow L. sphaericus isolate Bs2-1-2. Cell growth and endospore production were observed every 12 hours for 72 hours. The lethal concentration was measured every 24 hours for 72 hours of fermentation. The highest cell concentration was found in L. sphaericus grown on the media with 30% fishmeal concentration (3.03x1008 cells/mL), followed by 20% concentration (2.43x1008 cells/mL) and the lowest at 10% concentration (2.20x1008 cells/mL). At the end of fermentation, the highest concentration was found in L. sphaericus grown on 30% fishmeal-based media (1.51x1008 cells/mL), followed by 20% media (6.95x1007 cells/mL) and 10% media (3.21x1007 cells/mL). After 72-hour incubation, the highest endospore concentration was achieved by L. sphaericus grown on 20% (2.51x1008 cells/mL) and 10% (2.19x1008 cells/mL) fishmeal-based media. Initial larval toxicity of L. sphaericus showed the highest mortality on 20 and 30% fishmeal-based media (both reaching 53.33%), while 10% fishmeal-based media gave only 26.67% larval mortality. The LC50 value at 72 hours was achieved by L. sphaericus cultured on 30% fishmeal-based media (2.47 x 1008 cells/mL), followed by 20% concentration (4.82 x 1008 cells/mL) and 10% concentration (9.01 x 1009 cells/mL). The conclusion of this study was all concentrations of fishmeal-based media could support cell growth, endospore production and larval toxicity induction of L. sphaericus.